One Health prevention and preparedness to vector-borne diseases: how should we deal with a multisectoral, multilevel and multigroup governance? - Claudia Robbiati; Alessia Milano; Silvia Declich; Maria Grazia Dente (BMC, 2024)
Abstract Introduction Multifactorial determinants of vector presence, distribution and ability of transmitting diseases, demand holistic approaches that consider eco-biosocial factors, such as One Health (OH), and engage institutions and communities to reduce vulnerability to vector-borne diseases (VBDs). Although the importance of multisectoral, multilevel and multigroup collaboration for prevention and preparedness to VBDs has been promoted by international guidance, evidence about practical experiences adopting a OH approach needs to be gathered and enabling factors for a successful governance highlighted. Methods This study included a rapid literature review coupled with a stakeholder consultation process. Results The peer-reviewed literature search identified 1674 articles and 13 articles were finally included in the review. The collaboration and coordination of different sectors and stakeholders allowed to focus resources, and share knowledge and perspectives. To support coordination and collaboration among the stakeholders synergistic interaction mechanisms were created, such as working groups and committees, and connection agents emerged as the main link between institution and communities. These synergies allowed to target the multidimensional drivers of VBDs, supported transversal capacity building and an holistic monitoring evaluation framework, and improved effectiveness and sustainability of the interventions. Conclusion A OH model highlighting enabling factors for multisectoral, multilevel and multigroup interventions for VBDs prevention and preparedness was developed to support decision-makers and key stakeholders to deal with a OH governance.